2023
DOI: 10.1002/bmc.5631
|View full text |Cite
|
Sign up to set email alerts
|

Study on the opening effect of eucalyptol on the blood–brain barrier and its brain pharmacokinetics

Abstract: Eucalyptol, a natural epoxide monoterpene, was found in rat brain tissue after oral administration in our previous study, suggesting that the compound may possess the ability to pass the blood–brain barrier (BBB). However, a few studies have demonstrated that eucalyptol does penetrate the BBB. The aims of this study were to determine the opening effect of eucalyptol on the BBB in rats, to establish and validate a method for the determination of eucalyptol in brain tissue, and to reveal its brain pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The decreased activity of GSK-3 in response to 1,8-Cineol could ameliorate advanced glycation end products, which can be identified by immunohistochemistry in the senile plaques and neurofibrillary tangles of Alzheimer’s disease [ 86 , 87 ]. In this context, it was recently shown that eucalyptol reveals an opening effect on the blood–brain barrier and thus provides a promising addition in the treatment of illnesses of the central nervous system and its brain pharmacokinetics [ 88 ].…”
Section: Influence On Distinct Biosynthetic Pathwaysmentioning
confidence: 99%
“…The decreased activity of GSK-3 in response to 1,8-Cineol could ameliorate advanced glycation end products, which can be identified by immunohistochemistry in the senile plaques and neurofibrillary tangles of Alzheimer’s disease [ 86 , 87 ]. In this context, it was recently shown that eucalyptol reveals an opening effect on the blood–brain barrier and thus provides a promising addition in the treatment of illnesses of the central nervous system and its brain pharmacokinetics [ 88 ].…”
Section: Influence On Distinct Biosynthetic Pathwaysmentioning
confidence: 99%
“…Apart from their ability to cross the blood-brain barrier [96,97], the fact that linalool and eucalyptol can be taken orally has an added value, as there is now increasing evidence that α-syn pathology appears in the gastrointestinal tract and enteric nervous system well before it makes its entrance in the brain [98]. In vivo studies of citron and sage essential oils, along with their primary components, linalool and eucalyptol, are the next logical step for further assessment of their anti-amyloidogenic properties.…”
Section: Discussionmentioning
confidence: 99%